Enabling digital parenting modules to help Malaysian parents nurture digitally resilient children - Mohamed, Shafizan; Wan Mohd Ghazali, Wan Norshira; Mohd Nasir, Nur Shakira (Communication and Media Centre (COMET), KIRKHS, IIUM, 2023)
Children who are digitally resilient are empowered to use the Internet and social media to acquire knowledge, develop new skills, utilise digital technologies, express and develop their personalities, and engage in a variety of other beneficial activities. Many parents, however, are still unaware of the best ways to digitally parent their children. As a result, they frequently adopt restrictive styles, limiting children's potential to reap the benefits of digital tools. Digital disparities in socioeconomics and culture exacerbate this problem. In Malaysia, there is still a large divide between the T-20, M-40, and B-40 in terms of digital access, use, and literacy. Additionally, Malaysian parents come from a variety of ethnic, religious, and cultural backgrounds, which influences their parenting style and acceptance of new technologies. Thus, this research proposed that by gaining a better understanding of the real constraints that Malaysian parents face in the digital world, effective digital parenting modules can be developed to assist them in becoming enabling digital parents capable of maximising digital opportunities and mitigating digital risks for their children.